Dyschromatosis symmetrica hereditaria with long hair on the forearms, hypo/hyperpigmented hair, and dental anomalies: Report of a novel ADAR1 mutation - Piranit Nik Kantaputra (2018)
We report on a father and his two children who are affected with dyschromatosis symmetrica hereditaria (DSH). Mutation analysis of ADAR1 gene demonstrated a novel splice acceptor site mutation in intron 10, IVS10-2A>C. The hair on the forearm of the affected father became longer, larger in diameter, and hypopigmented (white) after age 40 years. Hyperpigmented hair was also found in normal and hypopigmented skin. The colors of the hair and the skin did not correlate. Transmission electron micrography of cortical keratinocytes of the hair follicles showed that normal hair contained more keratinocytes than those of hyperpigmented and hypopigmented hair. The keratinocytes of the hyperpigmented hair were larger than those of normal and hypopigmented hair and those of the normal hair were larger than those of the hypopigmented hair. The affected daughter had dens evaginatus of the mandibular right second premolar and the son had dens invaginatus of the maxillary permanent lateral incisors. Expression of Adar1 gene during mouse tooth development is demonstrated. © 2012 Wiley Periodicals, Inc.